Emerging Epigenetic Therapies for the Treatment of Cardiac Fibrosis - Nerea Garitano; Laura Pilar Aguado-Alvaro; Beatriz Pelacho (Biomedicines)
Fibrosis is a pathological process characterized by excessive extracellular matrix (ECM) deposition, leading to tissue stiffening and organ dysfunction. It is a major contributor to chronic diseases affecting various organs, with limited therapeutic options available. Among the different forms of fibrosis, cardiac fibrosis is particularly relevant due to its impact on cardiovascular diseases (CVDs), which remain the leading cause of morbidity and mortality worldwide. This process is driven by activated cardiac fibroblasts (CFs), which promote ECM accumulation in response to chronic stressors. Epigenetic mechanisms, including DNA methylation, histone modifications, and chromatin remodeling, are key regulators of fibroblast activation and fibrotic gene expression. Enzymes such as DNA methyltransferases (DNMTs), histone methyltransferases (HMTs), histone acetyltransferases (HATs), and histone deacetylases (HDACs) have emerged as potential therapeutic targets, and epigenetic inhibitors have shown promise in modulating these enzymes to attenuate fibrosis by controlling fibroblast function and ECM deposition. These small-molecule compounds offer advantages such as reversibility and precise temporal control, making them attractive candidates for therapeutic intervention. This review aims to provide a comprehensive overview of the mechanisms by which epigenetic regulators influence cardiac fibrosis and examines the latest advances in preclinical epigenetic therapies. By integrating recent data from functional studies, single-cell profiling, and drug development, it highlights key molecular targets, emerging therapeutic strategies, and current limitations, offering a critical framework to guide future research and clinical translation.